Modeling and Optimal Operation of Hydraulic, Wind and Photovoltaic Power Generation Systems - Li, Chaoshun; Zeng, Yun; Xu, Beibei; Liu, Dong (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The transition to 100% renewable energy in the future is one of the most important ways of achieving "carbon peaking and carbon neutrality" and of reducing the adverse effects of climate change. In this process, the safe, stable and economical operation of renewable energy generation systems, represented by hydro-, wind and solar power, is particularly important, and has naturally become a key concern for researchers and engineers. Therefore, this book focuses on the fundamental and applied research on the modeling, control, monitoring and diagnosis of renewable energy generation systems, especially hydropower energy systems, and aims to provide some theoretical reference for researchers, power generation departments or government agencies.